Posttraumatic Stress Disorder and Complex Posttraumatic Stress Disorder in DSM‐5 and ICD‐11: Clinical and Behavioral Correlates - Hyland, Philip; Shevlin, Mark; Fyvie, Claire; Karatzias, Thanos (Journal of traumatic stress, 2018)
The American Psychiatric Association and the World Health Organization provide distinct trauma‐based diagnoses in the fifth edition of the Diagnostic and Statistical Manual (DSM‐5), and the forthcoming 11th version of the International Classification of Diseases (ICD‐11), respectively. The DSM‐5 conceptualizes posttraumatic stress disorder (PTSD) as a single, broad diagnosis, whereas the ICD‐11 proposes two “sibling” disorders: PTSD and complex PTSD (CPTSD). The objectives of the current study were to: (a) compare prevalence rates of PTSD/CPTSD based on each diagnostic system; (b) identify clinical and behavioral variables that distinguish ICD‐11 CPTSD and PTSD diagnoses; and (c) examine the diagnostic associations for ICD‐11 CPTSD and DSM‐5 PTSD. Participants in a predominately female clinical sample (N = 106) completed self‐report scales to measure ICD‐11 PTSD and CPTSD, DSM‐5 PTSD, and depression, anxiety, borderline personality disorder, dissociation, destructive behaviors, and suicidal ideation and self‐harm. Significantly more people were diagnosed with PTSD according to the DSM‐5 criteria (90.4%) compared to those diagnosed with PTSD and CPTSD according to the ICD‐11 guidelines (79.8%). An ICD‐11 CPTSD diagnosis was distinguished from an ICD‐11 PTSD diagnosis by higher levels of dissociation (d = 1.01), depression (d = 0.63), and borderline personality disorder (d = 0.55). Diagnostic associations with depression, anxiety, and suicidal ideation and self‐harm were higher for ICD‐11 CPTSD compared to DSM‐5 PTSD (by 10.7%, 4.0%, and 7.0%, respectively). These results have implications for differential diagnosis and for the development of targeted treatments for CPTSD. Resumen Spanish s by the Asociación Chilena de Estrés Traumático (ACET) Trastorno por Estrés Postraumático (TEPT) y Trastorno por Estrés Postraumático Complejo (TEPT‐C) en el DSM‐5 y el CIE‐11: Correlatos Clínicos y Conductuales CORRELATOS DEL TEPT Y TEPT‐C La Asociación Psiquiátrica Americana y la Organización Mundial de la Salud proporcionan diferentes diagnósticos basados en trauma en la quinta edición del Manual Diagnóstico y Estadístico (DSM‐5, por su sigla en inglés), y la próxima undécima versión de la Clasificación Internacional de las Enfermedades (CIE‐11, por su sigla en español), respectivamente. El DSM‐5 conceptualiza el Trastorno por Estrés Postraumático (TEPT) como un diagnóstico único, amplio, mientras que el CIE‐11 propone dos trastornos “hermanos”: TEPT y TEPT Complejo (TEPT‐C). Los objetivos de este estudio fueron: (a) comparar la prevalencia de TEPT/TEPT‐C según cada sistema diagnóstico; (b) identificar variables clínicas y conductuales que distingan el TEPT‐C de CIE‐11 y el TEPT; y c) examinar las asociaciones de diagnóstico para el TEPT‐C del CIE‐11 y el TEPT del DSM‐5. Participantes de una muestra clínica predominantemente femenina (N = 106) completaron escalas de autoreporte para medir TEPT y TEPT‐C de CIE‐11, TEPT de DSM‐5, depresión, ansiedad, trastorno de la personalidad límite, disociación, conductas destructivas, ideación suicida y autoagresiones. Significativamente más personas fueron diagnosticadas con un TEPT según los criterios DSM‐5 (90.4%) comparadas a aquellas diagnosticadas con TEPT y TEPT‐C de acuerdo a las guías de CIE‐11 (79.8%). El diagnóstico de TEPT‐C de CIE‐11 se distinguía del diagnóstico de TEPT de CIE‐11 por mayores niveles de disociación (d = 1.01), depresión (d = 0.63), y trastorno de la personalidad límite (d = 0.55). La asociación del diagnóstico con depresión, ansiedad e ideación suicida y autoagresiones fue más alta para el diagnóstico de TEPT‐C de CIE‐11 comparado con TEPT de DSM‐5 (por 10.7%, 4.0%, y 7.0%, respectivamente). Estos resultados tienen implicancias para el diagnóstico diferencial y para el desarrollo de tratamientos orientados al TEPT‐C. 抽象 Traditional and Simplified Chinese s by AsianSTSS Posttraumatic Stress Disorder (PTSD) and Complex PTSD (CPTSD) in DSM‐5 and ICD‐11: Clinical and Behavioural Correlates Traditional Chinese 標題: DSM‐5 與ICD‐11裡的創傷後壓力症(PTSD) 和複雜性PTSD(CPTSD):臨床及行為關連因素 撮要: 美國精神醫學學會與世界衛生組織, 分別在《精神疾病診斷與統計手冊第五版》(DSM‐ 5)和即將推出的《國際疾病與相關健康問題分類第十一版》(ICD‐11), 提供不同的創傷診斷標準。DSM‐5把創傷後壓力症(PTSD)介定為單一、廣泛的診斷;ICD‐11則提出, PTSD與複雜性PTSD(CPTSD)為兩種「同胞」病症。本研究目的為: (一) 比較基於兩種診斷系統得出的PTSD/CPTSD普遍率; (二) 找出ICD‐11裡區別CPTSD 與PTSD診斷的臨床及行為變量; (三) 檢視ICD‐11的CPTSD 與DSM‐5的 PTSD診斷之間的關連。本臨床樣本大部分為女性(N = 106)。樣本完成了測量以下項目的自評量表:ICD‐11介定的 PTSD 與CPTSD、DSM‐5介定的PTSD、抑鬱症、焦慮症、邊緣人格障礙、離解症、摧毀性行為、自殺意念和自殘。相比在ICD‐11受介定為有PTSD 及CPTSD 的患者(79.8%), 在DSM‐5的標準裡顯著有較多人得出PTSD診斷(90.4%)。在ICD‐11裡, 得到CPTSD 診斷跟得到 PTSD 診斷的分別在於前者有較高水平的離解(d = 1.01)、抑鬱(d = 0.63)、邊緣人格障礙(d = 0.55)。與DSM‐5 的PTSD診斷相比, ICD‐11的CPTSD當中的抑鬱症、焦慮症、自殺意念與自殘的診斷關連較大 (分別高出10.7%, 4.0% 與7.0%) 。研究結果有助鑒別診斷以及發展針對CPTSD的治療。 Simplified Chinese 标题: DSM‐5 与ICD‐11里的创伤后压力症(PTSD) 和复杂性PTSD(CPTSD):临床及行为关连因素 撮要: 美国精神医学学会与世界卫生组织, 分别在《精神疾病诊断与统计手册第五版》(DSM‐ 5)和即将推出的《国际疾病与相关健康问题分类第十一版》(ICD‐11), 提供不同的创伤诊断标准。DSM‐5把创伤后压力症(PTSD)介定为单一、广泛的诊断;ICD‐11则提出, PTSD与复杂性PTSD(CPTSD)为两种「同胞」病症。本研究目的为: (一) 比较基于两种诊断系统得出的PTSD/CPTSD普遍率; (二) 找出ICD‐11里区别CPTSD 与PTSD诊断的临床及行为变量; (三) 检视ICD‐11的CPTSD 与DSM‐5的 PTSD诊断之间的关连。本临床样本大部分为女性(N = 106)。样本完成了测量以下项目的自评量表:ICD‐11介定的 PTSD 与CPTSD、DSM‐5介定的PTSD、抑郁症、焦虑症、边缘人格障碍、离解症、摧毁性行为、自杀意念和自残。相比在ICD‐11受介定为有PTSD 及CPTSD 的患者(79.8%), 在DSM‐5的标准里显著有较多人得出PTSD诊断(90.4%)。在ICD‐11里, 得到CPTSD 诊断跟得到 PTSD 诊断的分别在于前者有较高水平的离解(d = 1.01)、抑郁(d = 0.63)、边缘人格障碍(d = 0.55)。与DSM‐5 的PTSD诊断相比, ICD‐11的CPTSD当中的抑郁症、焦虑症、自杀意念与自残的诊断关连较大 (分别高出10.7%, 4.0% 与7.0%) 。研究结果有助鉴别诊断以及发展针对CPTSD的治疗。